2019
DOI: 10.1080/14992027.2019.1601270
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic current focusing for loudness encoding in cochlear implants: a take-home trial

Abstract: Objective: This study aimed to evaluate a more energy-efficient dynamic current focussing (DCF) speechprocessing strategy after long-term listening experience. In DCF, tripolar stimulation is used near the threshold and loudness is controlled by the compensation coefficient r. A recent acute pilot study showed improved spectral-temporally modulated ripple test (SMRT) scores at low loudness levels, but battery life was reduced to 1.5-4 hours. Design: Within-subject comparisons were made for the clinical versus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 44 publications
2
23
0
1
Order By: Relevance
“…There is evidence for better speech discrimination with partial tripolar stimulation compared with monopolar stimulation (11), but another study finds no difference in pitch discrimination between tripolar and monopolar stimulation (12). More recently, a modified form of tripolar stimulation termed dynamic current focusing is purported to give better spectral resolution under certain conditions (13). Another proposed strategy is phased array stimulation, which aims to produce focused electrical stimulation at a particular site by sending a complex phase-shifted array of inverted currents as the stimulation signal to all other sites that tries to cancel out the effects of current spread (14).…”
mentioning
confidence: 99%
“…There is evidence for better speech discrimination with partial tripolar stimulation compared with monopolar stimulation (11), but another study finds no difference in pitch discrimination between tripolar and monopolar stimulation (12). More recently, a modified form of tripolar stimulation termed dynamic current focusing is purported to give better spectral resolution under certain conditions (13). Another proposed strategy is phased array stimulation, which aims to produce focused electrical stimulation at a particular site by sending a complex phase-shifted array of inverted currents as the stimulation signal to all other sites that tries to cancel out the effects of current spread (14).…”
mentioning
confidence: 99%
“…Their results showed an improvement in noise, but no improvement under quiet conditions. Another similar study found that when using dynamic focusing spectral resolution improved, but this did not extend to speech performance ( De Jong, Briaire, & Frijns, 2018 ). These studies show that while results are mixed, channel focusing has the potential to improve speech perception, particularly in noise.…”
Section: Discussionmentioning
confidence: 99%
“…However, in that study the order of testing was not fully counterbalanced between the strategies, such that ACE was never tested first, and so one cannot rule out the influence of practice effects (cf. de Jong et al, 2019). Psarros et al (2002) reported significant improvements on word identification in quiet when seven children were converted from the SPEAK to the ACE strategy, and, importantly, that performance deteriorated again when they were switched back to SPEAK.…”
Section: Commercially Available Strategiesmentioning
confidence: 98%
“…Unfortunately, this design is susceptible to practice effects, such that the improvement might for example be due to increased familiarity with the test materials (Psarros et al, 2002;Vermeire et al, 2010;de Jong et al, 2019). Indeed, the differences between test sessions observed with a smaller number of tested ears, whose implants were not reprogrammed, overlapped substantially with those having deactivated electrodes.…”
Section: Patient-specific (Bespoke) Programmingmentioning
confidence: 99%
See 1 more Smart Citation